Efficacy and safety of tregalizumab in patients with rheumatoid arthritis and an inadequate response to methotrexate: results of a phase IIb, randomised, placebo-controlled trial. Issue 4 (17th January 2018) - van Vollenhoven, Ronald F; Keystone, Edward Clark; Strand, Vibeke; Pacheco-Tena, Cesar; Vencovský, Jiří; Behrens, Frank; Racewicz, Arthur; Zipp, Daniela; Rharbaoui, Faiza; Wolter, Ralf; Knierim, Luise; Schmeidl, Rainer; et al.
Abstract : Objective: To evaluate the efficacy, biological activity and safety of tregalizumab in patients with active rheumatoid arthritis (RA) and an inadequate response to methotrexate (MTX). Methods: 321 patients were randomised (1:1:1:1) to placebo or tregalizumab 25, 100 or 200 mg once-weekly subcutaneously in addition to MTX treatment. Responders at week 12 continued the same treatment, and non-responders at week 12 were escalated to the next higher tregalizumab dose level or re-randomised from placebo to active treatment. After 24 weeks, patients could continue treatment with tregalizumab for 24 weeks (extension phase). The primary endpoint was the American College of Rheumatology 20% improvement criteria (ACR20) response rate at week 12. Safety and biological activity were monitored through week 48. Results: At week 12, ACR20 response rates were not statistically significantly different between placebo and any of the tregalizumab doses. Tregalizumab injections were well tolerated; most adverse events were mild to moderate and comparable among treatment and placebo groups. Biological activity was shown by dose-dependent CD4 downmodulation. Conclusion: Treatment with tregalizumab did not show significant clinical efficacy in patients with active RA compared with placebo but resulted in the expected biological effect on CD4 modulation. Tregalizumab was generally well tolerated, and no new safety findings were identified. Trial registration number: NCT01999192; Results .